Translation and translators before the professional project - Paloposki Outi (United Kingdom, 2022)
Translators of the past may have been a very different breed from the professional translators of today. In order to examine the notion of ‘translator’ in a historical perspective, this article looks at attribution of translatorship in the late 19th century Finland. Instances of the word ‘translator’ were identified and the uses of the word examined with the help of several different data sets. The material included text corpora, yearbooks, bibliographies, reviews and translation contracts, and the different contexts and circumstances in which translators were mentioned were studied. ‘Translator’ emerges as a designation in two different contexts: as a position in state administration, and as a role with regard to translated literature (fiction and non-fiction). Outside these contexts and roles, authors of translations are usually not called translators.